2018
DOI: 10.1177/0954407017752832
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol fuels for spark-ignition engines: Performance, efficiency and emission effects at mid to high blend rates for binary mixtures and pure components

Abstract: The paper evaluates the results of tests performed using mid-and high-level blends of the low-carbon alcohols, methanol and ethanol, in admixture with gasoline, conducted in a variety of test engines to investigate octane response, efficiency and exhaust emissions, including those for particulate matter. In addition, pure alcohols are tested in two of the engines, to show the maximum response that can be expected in terms of knock limit and efficiency as a result of the beneficial properties of the two alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…When blended with gasoline, methanol reduces the final boiling point of the fuel, potentially promoting spray evaporation (and hence reducing PN emissions) however the increased ∆H vap and high volatility (leading to possible flash evaporation) may lead to poor mixture preparation and potentially higher levels of PN emissions. With such a mixed effect, as might be expected, studies on PN emissions from methanol-gasoline blends have again showed mixed results [141,[152][153][154].…”
Section: Impact Of Methanol Fuel Blends On Gdi Pm Emissionsmentioning
confidence: 76%
See 1 more Smart Citation
“…When blended with gasoline, methanol reduces the final boiling point of the fuel, potentially promoting spray evaporation (and hence reducing PN emissions) however the increased ∆H vap and high volatility (leading to possible flash evaporation) may lead to poor mixture preparation and potentially higher levels of PN emissions. With such a mixed effect, as might be expected, studies on PN emissions from methanol-gasoline blends have again showed mixed results [141,[152][153][154].…”
Section: Impact Of Methanol Fuel Blends On Gdi Pm Emissionsmentioning
confidence: 76%
“…E5 (up to 5% by volume of ethanol in gasoline) blends are ubiquitous in Europe, with E10 and E15 common in the USA; E85 is also common, although requiring vehicles that have been specially adapted (so-called flex-fuel vehicles); E100 is common in Brazil [136,137]. A number of recent studies on the influence of oxygenated fuel blends on PM emissions from GDI engines have been reported [1,85,114,[138][139][140][141]. Typically oxygenated fuels have higher vapour pressures, significantly higher ∆H vap (kJ/kg stoichiometric mixture), and significantly lower LHVs compared to gasoline.…”
Section: Impact Of Oxygenated Fuels On Gdi Pm Emissionsmentioning
confidence: 99%
“…Alcohol blending can take the form of low-, mid-and high-level blends, for which there is no formal definition, but which Turner et al considered to be up to 15% by volume (low), 15-30% (mid) and over 30% by volume (high) [57]. Israel recently adopted an M15 standard [58].…”
Section: Binary Alcohol Blendsmentioning
confidence: 99%
“…As an alternative fuel with great application potential, many researchers have tested methanol on spark ignition (SI) engines and compression ignition (CI) engines or other engines work with new combustion strategies. Turner [6] et al tested methanol-gasoline blends on an SI engine, they figured that methanol provides a much higher knock limit and gives great improvements in thermal efficiency compared with pure gasoline. Avinash et al [7] found methanol can increase brake thermal efficiency (BTE) and made a lower emission of NO x , CO and smoke opacity for its higher latent heat of evaporation between NOx emissions and fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Ladommatos et al [21][22][23][24] also pointed out that dilution effect of EGR is the dominate cause of the NOx reduction through experiments on a diesel engine. According to Turner, methanol allows using EGR for lean burn to a higher degree than gasoline on a high-CR engine, so methanol is a suitable fuel for high-CR SI lean burn engine [6].Although it has been proved that EGR can improve engine performance, the specific role of its internal components, it is not clear which is required to study further. Exhaust gas contains nitrogen (N 2 ), carbon dioxide (CO 2 ) and argon (Ar).…”
mentioning
confidence: 99%